2004
DOI: 10.1300/j013v40n01_01
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Strength Training in Older Rural African American and Caucasian Women

Abstract: This study examined factors influencing strength training (ST) in two convenience samples of older rural women. Focus group (FG) participants were 23 Caucasian and 16 African American women aged 67.5 +/- 9.2 years. Survey participants were 60 Caucasian and 42 African American women, aged 70.59 +/- 9.21 years. FG participants answered questions about the risks, benefits, and barriers to ST. Survey participants completed measures of demographics, physical activity (including ST), depression and stress, decisiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
90
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(92 citation statements)
references
References 27 publications
(30 reference statements)
1
90
1
Order By: Relevance
“…Two studies reported a positive association between family support and participating in RT, with small effects,54 56 while one study39 reported a similar positive relationship in the first 3 months of RT participation but no relationship at 6 months. In one study, there was a small positive association between friend support and participating in RT,56 while one study showed no association 54. Six qualitative studies found that peer support was a key factor for participating in RT, and one quantitative study39 showed no association.…”
Section: Resultsmentioning
confidence: 96%
“…Two studies reported a positive association between family support and participating in RT, with small effects,54 56 while one study39 reported a similar positive relationship in the first 3 months of RT participation but no relationship at 6 months. In one study, there was a small positive association between friend support and participating in RT,56 while one study showed no association 54. Six qualitative studies found that peer support was a key factor for participating in RT, and one quantitative study39 showed no association.…”
Section: Resultsmentioning
confidence: 96%
“…The mean age of participants among the 26 studies providing sufficient data for calculation was 47.9 years (encompassing a total of 4188 participants). Additionally, five studies had samples comprised of mostly low-income women (Evans, 2011; Hoebeke, 2008; Kirchoff et al 2008; Lee et al 2011; Wilbur et al 2002; Wilcox et al 2005) and the remainder of studies included women with diverse income levels (n=28) or lacked sufficient information to determine the income levels of participants (n=9; Bopp et al 2004; Bopp et al 2006; Dunn 2008; Eyler et al 1998; Wilcox et al 2002; Im et al 2012; Sanderson, Littleton and Pully 2002; D’Alonzo and Fischetti 2008; Richter et al 2002). Only one study (Doldren and Webb 2013) provided information the regarding the ancestry or ethnic background of AA women enrolled in the study.…”
Section: Resultsmentioning
confidence: 99%
“…However, few studies based on such viewpoints have been studied in Japan. In the US, studies on elderly people have pointed out that social support affected engagement of strength training (Bopp et al, 2004) and that subjective norms and perceived behavioral control for social expectations were correlates of the strength training behavior (Dean et al, 2007). In the future, it will be strongly required to examine factors that may affect the strength training behavior from broad-ranging viewpoints taking into account environmental factors.…”
Section: Discussionmentioning
confidence: 99%